Refleksja nad wychowaniem dziecka w bezpiecznym stylu więzi = Reflection on upbringing of a child promoting secure attachment - Jędrzejowska, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The text presents the importance of attachment with a caregiver for the proper development of the child. It describes categories of attachment, focusing mainly on the qualities of the secure attachment, presenting some selected principles of its construction. The article also characterizes the parent/caregiver who is to recognize and meet the needs of the child. This approach is a safe base and prerequisite to help the child reach autonomy.
Keywords: więź; potrzeby dziecka; autonomia; bezpieczna baza; zachowania przywiązaniowe i eksploracyjne; attachment; child`s needs; autonomy; secure base; attachment and exploratory behaviour